Influence of Weather Factors on the Incidence and Distribution of Pumpkin Beetle Infesting Cucurbits (Bangladesh Journal of Agricultural Research, 2012)
Not available DOI: http://dx.doi.org/10.3329/bjar.v37i2.11241 Bangladesh J. Agril. Res. 37(2): 361-367, June 2012